Pemberdayaan Pelaku UMKM melalui Sosialisasi Pengembangan dan Pemasaran Produk Kripik Pisang Lumer di Desa Widoro, Trenggalek - Hasby Wisnu Firmansyah; Ahmad Fauzan; Ahmad Fahrudin; Luthfi Abdul Manaf; Muhammad Zen Masruri (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose: Local processed products such as banana chips have high economic potential if developed and marketed effectively. However, limited knowledge of product innovation and marketing strategies remains a major constraint for micro-enterprise actors. This community service activity aimed to enhance the understanding of MSME actors in Widoro Village regarding product development through banana chips innovation, specifically kripik pisang lumer, and its marketing strategies. Method: The program was conducted using a Service Learning approach, where students designed and facilitated socialization activities, production training, and education on branding and marketing. The materials included processing techniques for banana chips with a “lumer” variation, flavor innovation, packaging design, and the utilization of social media and digital marketing for product promotion. Practical Applications: The activity involved PKK members and home-based food processing entrepreneurs. Participants were trained to produce crispy banana chips with higher selling value and were encouraged to identify local and digital market opportunities, as well as to create attractive packaging with simple product labeling. Conclusion: The training successfully improved participants’ knowledge and skills in product innovation and marketing. Banana chips with a “lumer” concept show strong potential to become a superior village product if sustainably developed, supported by collaborative and contextual community engagement.